Pengaruh Peran Orang Tua Dan Motivasi Belajar Siswa Terhadap Hasil Belajar Matematika Siswa Pada Masa Pandemi Covid-19 - Yustika Sariamas; James U.L Mangobi; Derel F. Kaunang (Universitas Islam Jember, 2023)
This research aims to determine the effect of the role of parents’ and students' learning motivation on students' mathematics learning outcomes during the Covid-19 pandemic. This type of research is quantitative using survey methods. This research was conducted at Public Junior High School 6 Kotamobagu in the even semester of the 2020/2021 academic year. The population in this study were all students of class VIII consisting of 4 classes totaling 127 students. Data collection techniques using questionnaires and documentation. The questionnaire used revealed the variables of the role of parents and students' learning motivation, while the documentation revealed the results of students' mathematics learning taken from the grade VIII students' report cards for the even semester of the 2020/2021 academic year at Junior High School 6 Kotamobagu. The data analysis that will be used to test the hypothesis in this study is multiple linear regression analysis. The results of the study showed that there was a positive influence on the role of parents and student learning motivation on students' mathematics learning outcomes during the covid-19 pandemic, with the regression equation obtained from the results of the hypothesis test being, and, , and then a coefficient of determination of 0,473. It can be concluded that there was an influence of the role of parents and student learning motivation on student mathematics learning outcomes during the covid-19 pandemic of 47.3%. Keywords: parenting role, students learning motivation, mathematical learning outcomes